2020
DOI: 10.21307/sjcapp-2020-004
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying: relationship with developmental variables and cyber victimization

Abstract: Background and objective: Cyberbullying is increasingly turning into a significant problem for children and adolescents due to its adverse psychological and academic outcomes. In the present study, the protective and risk factors for cyberbullying has been investigated. One of the aims of the study was to examine the relationship between peer relations, negative emotion regulation strategies, and cyberbullying. The successful identity development process is thought to influence both cyberbullying behaviors as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
0
6
0
4
Order By: Relevance
“…In another study across three time points, CV at a given time point marginally predicted CB at a subsequent time point (Chu et al, 2018). Results from hierarchic regression analysis and cross-lagged panel model also showed the significant prediction of CV at time 1 on CB at time 2 (Akgül & Artar, 2020). Despite the weak effects, these longitudinal findings provide some support to the directional effect from CV to CB.…”
Section: From Cybervictimisation To Cyberbullyingmentioning
confidence: 80%
See 2 more Smart Citations
“…In another study across three time points, CV at a given time point marginally predicted CB at a subsequent time point (Chu et al, 2018). Results from hierarchic regression analysis and cross-lagged panel model also showed the significant prediction of CV at time 1 on CB at time 2 (Akgül & Artar, 2020). Despite the weak effects, these longitudinal findings provide some support to the directional effect from CV to CB.…”
Section: From Cybervictimisation To Cyberbullyingmentioning
confidence: 80%
“…But results from a structural equation model across three time points showed that CB at a given time point marginally predicted CV at a subsequent time point. In Akgül and Artar (2020), CB at time 1 also significantly associated with CV at time 2 but the effect was not significant after controlling for CV at time 1 in both hierarchic regression model and cross-lagged panel model. Similar to the findings for the effect of CV on CB, although not all findings provide clear causal evidence, most demonstrated that CV is longitudinally associated with prior CB.…”
Section: From Cyberbullying To Cybervictimisationmentioning
confidence: 81%
See 1 more Smart Citation
“…Siber zorbalık, başkalarını rahatsız etmek veya korkutmak amacıyla elektronik veya dijital medya aracılığıyla sürekli olarak düşmanca veya saldırgan mesajlar ileten kişi veya gruplar tarafından gerçekleştirilen davranışlardır (3,5,9,10). Türkiye'de ve uluslararası alanda yapılan çalışmalarda, öğrenciler arasında siber zorbalık ve mağduriyetin çok sık karşılaşılan bir sorun olduğu belirlenmiştir (3,7,8,(11)(12)(13). Gençler arasında yaygın bir sorun olan siber zorbalık, bireyin duygusal, sosyal ve psikolojik gelişimine zarar vermekle birlikte, toplumsal ilişkileri de olumsuz yönde etkileyebilmektedir (3,5,9,10,14,15).…”
Section: Introductionunclassified
“…Normal gelişimsel süreç, geleceğe ilişkin hayaller, sınavlar, akran ilişkileri, sevilen bir kişinin kaybı gibi yaşam olayları adölesanlar için stres yaratabilir (22). Adölesanlar stres ve öfkeleri ile baş etmek ya da çevrim içi ortamlarda kimlik araştırması yapabileceklerinden internet ile ilgilenebilirler (11). Bu nedenle adölesan dönem, stres ve öfke; internet bağımlılığı ve siber zorbalık ile ilişkilendirilebilir (11,18).…”
Section: Introductionunclassified